PENGARUH PERUBAHAN TARIF PAJAK, PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PADA TAHUN 2008-2012 - Sekar Utami, Luh Noviana; Widanaputra, Anak Agung Gede Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study aims to determine the effect of tax rates, profitability, liquidity, and the size of the company's capital structure. This study uses leverage as a proxy of the y capital y structure. The sample in this study are 193 companies listed in Indonesia Stock Exchange 2008-2012 period. Samplin was done by purposive sampling method. Classic assumption test using the test for normality, heteroscedasticity, multicollinearity, and autocorrelation. The regression analysis used is multiple linear regression analysis. Based on the discussion of research results prove that the corporate income tax rate negatively affect capital structure. Profitability negative effect on the capital structure. Then liquidity negatively affect the capital structure. While the size of the positive effect on the company's capital structure.
Keywords: tax rates, profitability, liquidity, company size, capital structure